Ultraviolet photoacoustic remote sensing microscopy - Haven, Nathaniel J M; Bell, Kevan L; Kedarisetti, Pradyumna; Lewis, John D; Zemp, Roger J (Optics letters, 2019)
Traditional histopathology involves fixing, sectioning, and staining protocols that are time consuming and subject to staining variability. In this Letter, we present ultraviolet photoacoustic remote sensing microscopy, capable of imaging cell nuclei without the need for exogenous stains or labelling. Our reflection mode approach is non-contact and has the potential to provide useful histological information without laborious sample preparation steps. Tumor cell cultures and excised tissue samples were imaged with the 0.7 μm resolution and signal-to-noise ratios as high as 53 dB, with close agreement to traditional hematoxylin and eosin staining.